EFEKTIVITAS PENGGUNAAN MEDIA MAKET TERHADAP HASIL BELAJAR KELAS X MAS AL-MUSTAQIM KUBU RAYA - Rocky Herlianto; Sulistyarini Sulistyarini; Ika Rahmatika Chalimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe aims of this research to knowing the effectivitieness of models media to learning outcomes. The research was conducted applying pre-experimental design with planning the one-group pretest-posttest design. This populations in the research was 10th-grade student of MAS Al-Mustaqim and this subjek was 10th-IPS1 student. The technique of data collection were direct observation technique, direct comunication technique, measurement technique, and study document technique. The tools of data collecting in this research were notebook, interviews and learning outcomes in the form of pretest and posttest. The result of normality test state that the results of residual values are normally distributed with a significant value of 0,586 > 0,05. While the result of the hypothesis test state that Ho is rejected and Ha is accepted based on the sig value. The pretest average value is 53,75 and the posttest average value is 78,75. The Value of Cohen Effect Size is 1,48 including on high category. So, the conclusion of apply models media on history subject is effectiveness for student learning outcomes in 10th-grade IPS 1 Mas Al-Mustaqim Kubu Raya. Keywords: History Subjects, Learning Outcomes, Media Mockup